Edukasi Kader Dasawisma (Enggan Vaksinasi) Terkait Pengetahuan Vaksinasi Covid-19 di Jakarta Timur - Ayu Magdalena Natalia Situmeang; Laily Hanifah (Jurnal Kesehatan Komunitas, 2022)
Vaccination is an important part of the Covid-19 response strategy which aims to slow and stop the rate of transmission. Dasawisma cadres as the government's pillar in the success of the Covid-19 vaccination program, but there are still many dasawisma cadres in East Jakarta who are not ready to be vaccinated. Therefore, health education is carried out online for dasawisma cadres, by presenting knowledge-related materials on vaccines and distributing e-posters containing information related to vaccines. The study was aimed to provide new knowledge and views regarding Covid-19 vaccination, so that cadres and the public no need to hesitate about getting vaccinated. The study followed a pre-experimental design in which a pretest and posttest was given to the sample, and using quota sampling (up to 500 cadres) for sampling method. A Wilcoxon Signed Rank Test is used to calculate the degree of significance of increasing cadres’ knowledge about vaccination, it was known that asymp sig = 0.000, from 39 cadres with good knowledge (before health education) to 427 cadres with good knowledge after health education,  which means that there is a significant difference in the level of knowledge of the audience before and after the intervention. Dasawisma cadres are the right target for the stated objectives, namely to provide new knowledge and views regarding vaccination. Thus, this health education can be considered successful in increasing the knowledge of dasawisma cadres regarding Covid-19 vaccination.